The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00784-021-04328-2
|View full text |Cite
|
Sign up to set email alerts
|

Immediately provisionalized tapered conical connection implants for single-tooth restorations in the maxillary esthetic zone: a 5-year prospective single-cohort multicenter analysis

Abstract: Objectives This open, single-cohort, multicenter, prospective study investigated the efficacy of immediately provisionalized tapered conical connection implant for single-tooth restorations in the anterior and premolar regions of the maxilla after 5 years of function. Materials and methods All implants were placed in healed sites and immediately provisionalized. MBLs, soft-tissue parameters, and oral-health impact profile (OHIP) were evaluated at implant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Assuming that the alveolar bone is the basis for the dental implants function according to their purpose in the act of biting and mastication [ 11 , 12 ], other factors such as soft tissue condition, depth of gingival pockets, gingival biotype, width of the keratinized gingival zone, color and translucency of soft tissues [ 13 , 14 , 15 ] are, however, secondary. In recent years, increasing attention has been paid to the phenomenon of corticalization [ 16 , 17 , 18 ]. It had been hypothesized that after bone remodeling of bone above the implant neck, almost no bone loss could be expected [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the alveolar bone is the basis for the dental implants function according to their purpose in the act of biting and mastication [ 11 , 12 ], other factors such as soft tissue condition, depth of gingival pockets, gingival biotype, width of the keratinized gingival zone, color and translucency of soft tissues [ 13 , 14 , 15 ] are, however, secondary. In recent years, increasing attention has been paid to the phenomenon of corticalization [ 16 , 17 , 18 ]. It had been hypothesized that after bone remodeling of bone above the implant neck, almost no bone loss could be expected [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…How to measure the product quantity derived from corticalization process in peri-implant bone in a clinical situation is a critical question. In recent years, the occurrence of corticalization in peri-implant bone was mentioned in scientific literature [32,[34][35][36], and attempts are being made to describe this phenomenon [3] and get to know its clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the present study showed an initial mean bone loss of 0.40 mm (SD = 0.48) after 6 months and minimal bone level changes over time up to 5 years in function. While the small sample size of this uncontrolled study limits direct comparisons to findings in other studies, these findings suggest that crestal bone loss around TM implants is lower than traditional titanium implant systems [13,14], and that the unique properties of PTTM may foster enhanced vital bone and surrounding tissue ingrowth and potentially reduce the amount of bone remodeling which occurs during the first year following implant surgery [15].…”
Section: Discussionmentioning
confidence: 99%